2007
DOI: 10.1152/ajpheart.00062.2007
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic reactivation after repeated sprint exercise

Abstract: Buchheit M, Laursen PB, Ahmaidi S. Parasympathetic reactivation after repeated sprint exercise. Am J Physiol Heart Circ Physiol 293: H133-H141, 2007. First published March 2, 2007; doi:10.1152/ajpheart.00062.2007.-The purpose of this study was to examine the effects of muscular power engagement, anaerobic participation, aerobic power level, and energy expenditure on postexercise parasympathetic reactivation. We compared the response of heart rate (HR) after repeated sprinting with that of exercise sessions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
305
3
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(357 citation statements)
references
References 55 publications
38
305
3
11
Order By: Relevance
“…The frequency domain methods are perhaps the most widely used in exercise/training studies investigating HRV, but they have methodological limitations that inhibit their use during changing autonomic conditions, like immediate recovery after exercise (Task Force, 1996). In the few studies that have investigated HRV recovery during the first minutes of recovery, HRV has been found to be significantly lower than resting values, and either starting to increase already during the first recovery minutes (Casties et al 2006;Goldberger et al 2006;Martinmäki & Rusko, 2008) or remaining blunted for several minutes before recovery begins (Buchheit et al 2007a;Oliveira et al 2013). Differences in the results may be, at least partly, explained with differences in the physical TL of the preceding exercises as well as in the training status of the subjects.…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…The frequency domain methods are perhaps the most widely used in exercise/training studies investigating HRV, but they have methodological limitations that inhibit their use during changing autonomic conditions, like immediate recovery after exercise (Task Force, 1996). In the few studies that have investigated HRV recovery during the first minutes of recovery, HRV has been found to be significantly lower than resting values, and either starting to increase already during the first recovery minutes (Casties et al 2006;Goldberger et al 2006;Martinmäki & Rusko, 2008) or remaining blunted for several minutes before recovery begins (Buchheit et al 2007a;Oliveira et al 2013). Differences in the results may be, at least partly, explained with differences in the physical TL of the preceding exercises as well as in the training status of the subjects.…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 99%
“…They concluded that restoration of autonomic control of HR is slower after exercise with a greater metabolic demand (Martinmäki & Rusko, 2008). In addition to Martinmäki & Rusko (2008), Buchheit et al (2007a) concluded that parasympathetic reactivation appears to be mainly related to anaerobic process. They studied the effects of high-intensity sprint exercises on immediate 10 min HRV recovery of trained athletes, and found highly impaired vagal reactivation during the first minutes of recovery.…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…When addressing autonomic factors that interfere on blood pressure, heart rate variability (HRV) is the best indirect method to evaluate the autonomic control over the cardiovascular system for humans 21 . Vagalrelated indexes, such as the power density in the high-frequency (HF) range obtained by spectral analysis, are the most widely used variables to examine HRV 22 . At rest there is a predominance of vagal modulation of the heart, but during exercise sympathetic tone is increased and parasympathetic tone diminishes gradually 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have assessed the REC-HR after aerobic exercise and observed that exercise intensity 13 , aerobic fitness 14 , physical training 15 , among other factors, influence on the behavior of this variable. On the other hand, despite the high number of practitioners, few studies have been carried out in the attempt to evaluate the REC-HR after the RE 7,8 .…”
Section: Introductionmentioning
confidence: 99%